CURRENT ACCOUNT DEFICIT AND ECONOMIC GROWTH IN ARMENIA - Tunian, Arus (Studies and Scientific Researches. Economics Edition, 2015)
The article is devoted to the study of the problem of economic growth in Armenia. It is identified the nature of the balance of payments of the country, indicating a net debtor position, which leads to inherent deterioration of the international investment position. A small open economy of Armenia moves to a new phase of development, in the frame of the integration processes within the Customs Union and the Eurasian Economic Union of Russia, Belarus and Kazakhstan. One of the main characteristics of the Armenian economy vulnerability remains a negative balance in foreign trade, which continues to grow, despite the export growth. Economic growth is provided, as before, mostly due to the sale of raw materials - non-ferrous metals and metal ores, both in the primary as well as in the previous preprocessing. Estimating the econometric VAR models revealed that the negative current account impacts on GDP growth negatively.